DAMPAK PEMEKARAN KECAMATAN PAUH TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT KECAMATAN PAUH KOTA PADANG TAHUN 1982-2010 - sy, Rahmayeni; Sabar, Sabar; Aziz, Zulkifli (Pendidikan Sejarah, 2014)
This research is astudy of social economy history by selecting title the effect of the developing of Pauh subdistrict to social economy living of Pauh subdistrictâs society, Padang, 1982-2010, is an interesting matter to be discussed, because with the presence of the developing effect in Pauh subdistrict can change the economic well. This research belongs to history research so that this study follows history method that is heuristic, critic, interpretation,historiography of research result in from of paper (thesis).The effect of the developing in an area can bring changes in government arrangement and pattern og social economy living in Pauh, people will experience area autonomy and people who work in agriculture field such as, the farmer of coffee, cinnamon, chili, earning changing even to the better living is a reality in human life. The changes happen everywere including Pauh subdistrict, Padang, west Sumatera. Pauh subdistrict has promising potential in agriculture, the changing process in Pauhâs society in 1995, the society is more interested to earn a living by building shop such as clothes shop, shoe shop, restaurantt, uniform store, compared to society who work in agricultural field. The changing on economic aspect,especially the changing of societyâs profession by focusing attention to the agricultural to fulfill daily needs which is supported by many suporting factors of society to focus on organizing agriculture, where in this limitation research started from 1982-2010.Pauh is an area which is made for brading and developing of padang. Making the. In short study, there is research result which describe the effect of the developing that is done by government regulation legally based an PP No. 17 1980 and to the society and niniak mamak, by this developing on 1982, can change thinking in agricultural to repair family economi.